2008
DOI: 10.1007/s10695-008-9247-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative responses in rare minnow exposed to 17β-estradiol during different life stages

Abstract: Present in the excrement of humans and animals, 17beta-estradiol (E(2)) has been detected in the aquatic environment in a range from several nanograms to several hundred nanograms per liter. In this study, the sensitivities of rare minnows during different life stages to E(2) at environmentally relevant (5, 25, and 100 ng l(-1)) and high (1000 ng l(-1)) concentrations were compared using vitellogenin (VTG) and gonad development as biomarkers under semistatic conditions. After 21 days of exposure, VTG concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 41 publications
3
16
0
1
Order By: Relevance
“…Regulation of circulating E2 by ERs is an important regulator of ovarian development in fish and is interlinked with growth and development (Devlin and Nagahama, 2002). Estrogen receptors increase in number during development, and in particular are likely to increase rapidly prior to and during sexual differentiation and reproduction (Liao et al, 2009), and transcription of different isoforms shifts periodically throughout early development (Chandrasekar et al, 2010). Gonad differentiation begins early in development in Atlantic salmon, as many of the major genes involved in sex determination and differentiation are upregulated in the embryonic stage (von Schalburg et al, 2011).…”
Section: ␣-Ethinylestradiolmentioning
confidence: 99%
“…Regulation of circulating E2 by ERs is an important regulator of ovarian development in fish and is interlinked with growth and development (Devlin and Nagahama, 2002). Estrogen receptors increase in number during development, and in particular are likely to increase rapidly prior to and during sexual differentiation and reproduction (Liao et al, 2009), and transcription of different isoforms shifts periodically throughout early development (Chandrasekar et al, 2010). Gonad differentiation begins early in development in Atlantic salmon, as many of the major genes involved in sex determination and differentiation are upregulated in the embryonic stage (von Schalburg et al, 2011).…”
Section: ␣-Ethinylestradiolmentioning
confidence: 99%
“…Due to the estrogen control of VTG, levels of this protein have been found to be an effective biomarker for estrogen exposure in fish. Many of the articles reviewed for this paper used VTG induction as a marker of estrogen exposure and response, and many found VTG induction at environmentally relevant concentrations of E 1 , E 2 , EE 2 and E 3 (Bogers et al , ; Fenske et al , ; Holbech et al , ; Länge et al , ; Liao et al , ; Örn et al , ; van Aerle et al , ). Further, Tyler et al () found induction of this protein to be a more sensitive endpoint than changes on sex ratios or sex reversal in juvenile fathead minnows exposed to 17 β ‐E 2 .…”
Section: Effects Of Steroid Hormones On Fish Early Life Stagesmentioning
confidence: 99%
“…Gobiocypris rarus has been widely used as an important model animal for studies with their small size, ease of laboratory culture, wide temperature range, short life cycle, high fertilization rate and hatching rate, sensitivity to chemicals, and many other advantages, and rare minnow are promising animal model for aquatic toxicology research (Wang 1999). Recently, several studies have documented endocrine-disrupting effects in G. rarus (Zha et al 2007(Zha et al , 2008aLiao et al 2009;Wang et al 2010Wang et al , 2011.…”
Section: Introductionmentioning
confidence: 99%